Effect of Steam Flow Rate and Storage Period of Superhydrophobic-Coated Surfaces on Condensation Heat Flux and Wettability - Fedorova, Nataliia; Lindner, Christian; Prado, Lucia; Jovicic, Vojislav; Zbogar-Rasic, Ana; Virtanen, Sannakaisa; Delgado, Antonio (Multimodal Technologies and Interaction, 2021)
The jumping-droplet phenomenon occurring on superhydrophobic (SHPhob) surfaces under special conditions may be beneficial for numerous systems using condensation, due to the reported increased heat transfer coefficients. One technique to create a SHPhob surface is coating, which can be applied to larger areas of existing elements. However, challenges are associated with coating stability and the realization of continuous dropwise condensation. This research examined the condensation of steam at different flow rates (2, 4 and 6 g/min) and its influence on heat flux and water contact angles on the SHPhob spray-coated aluminum samples. Special emphasis on the impact of time was addressed through a series of one and five-hour condensation experiments on the samples with different storage periods (coated either one year ago or shortly before testing). Over the experimental series at a higher steam flow rate (6 g/min), heat flux decreased by 20% through the old-coated samples and water contact angles transferred from the superhydrophobic (147°) to hydrophobic (125°) region. This can be attributed to the joint effects of the partial coating washout and the adsorption of the condensed water within the porous structures of the coating during steam condensation. The new-coated samples could sustain more than fifty hours of condensation, keeping the same heat fluxes and SHPhob characteristics.
Keywords: condensation heat transfer; steam flow rate; superhydrophobicity; coating; stability; contact angle